Fundamental Analysis of PT. Bank Syariah Indonesia, Tbk Post Covid-19 Pandemic - Much. Mabrur Hadi (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
The Covid-19 pandemic has had an impact on the financial sector including banking and capital markets. What is the description of the condition of banking issuers in the capital market after the Covi-19 pandemic? This study aims to describe how the fundamental analysis of PT. Bank Syariah Indonesia, Tbk after the Covid-19 pandemic. This research includes qualitative and quantitative descriptive research with research methods using two data analysis techniques, namely content analysis of the results of literature study and fundamental analysis of the performance of financial reports. The data used is secondary data in the form of PT. Bank Syariah Indonesia, Tbk and other publications relevant to research. The results of the study show that after the Covid-19 pandemic, PT. Bank Syariah Indonesia, Tbk is an issuer that fundamentally has very good financial report performance. Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS) PT. Bank Syariah Indonesia, Tbk as several instruments in conducting a fundamental analysis of the shares of PT. Bank Syariah Indonesia, Tbk shows a positive increase between 2020-2022. This is expected to be a reference for investors to determine their investment decision making both in the short term and in the long term related to the issuer of PT. Indonesian Sharia Bank, Tbk.